Non – Invasive, smartphone image-based screening for sickle cell disease at the point-of-need - Eudorah F. Vital; Meredith Haak LiCalzi; Robert G. Mannino; Patrick T. McGann; Wilbur A. Lam (Heliyon)
Leveraging the increasing accessibility of smartphones in healthcare settings, we developed a smartphone app aimed at enhancing sickle cell disease (SCD) screening, particularly in resource-limited settings. Our application provides accurate and non-invasive SCD screening with instant results at the point-of-need. The app operates by analyzing patient fingernail images via a smartphone image to gauge anemia severity and by using targeted inquiries to identify SCD-related symptoms. These inputs collectively generate an SCD IMage and Patient profile-based Likelihood Estimation (SIMPLE) score, which estimates disease probability. The accuracy of the score depends on two inputs: the patient's anemia status and their health survey responses. We tested the app on 485 pediatric patients at Children's Healthcare of Atlanta (CHOA), achieving an overall sensitivity of 74 % and specificity of 76 % in screening for SCD among children aged 6 months to 21 years. Notably, the app demonstrated enhanced performance in the target demographic, with 100 % sensitivity and 75 % specificity for screening SCD in children aged 6 months to 5 years. This cost-effective and scalable app efficiently pinpoints and stratifies individuals, particularly those who missed early screening, for formal screening programs.